2018
DOI: 10.1088/1361-6463/aab146
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dynamics of bovine aortic smooth muscle cells measured using MEMS force sensors

Abstract: Adhesive cells perceive the mechanical properties of the substrates to which they adhere, adjusting their cellular mechanical forces according to their biological characteristics. This mechanical interaction subsequently affects the growth, locomotion, and differentiation of the cell. However, little is known about the detailed mechanism that underlies this interaction between adherent cells and substrates because dynamically measuring mechanical phenomena is difficult. Here, we utilize microelectromechamical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Two electrodes were placed at the roots of the two hinges and the resistance of the cantilever is defined as the resistance between the two electrodes. The fabrication process of the cantilever can be found in previous studies [24][25][26][27][28][29]. A photograph of the fabricated sensor chip attached and wire-bonded to a flexible substrate and a photograph of the cantilever are shown in Figure 2a.…”
Section: Piezoresistive Cantilevermentioning
confidence: 99%
See 1 more Smart Citation
“…Two electrodes were placed at the roots of the two hinges and the resistance of the cantilever is defined as the resistance between the two electrodes. The fabrication process of the cantilever can be found in previous studies [24][25][26][27][28][29]. A photograph of the fabricated sensor chip attached and wire-bonded to a flexible substrate and a photograph of the cantilever are shown in Figure 2a.…”
Section: Piezoresistive Cantilevermentioning
confidence: 99%
“…A differential pressure in the range of ±10 Pa was applied to the cantilever using a pressure generator. The fractional resistance change of the cantilever was measured using the setup reported in previous studies [24][25][26][27][28][29][30][31][32], which consists of the Wheatstone bridge circuit and an amplifying circuit whose output is recorded using a ScopeCorder (Yokogawa Test & Measurement Co., Tokyo, Japan, DL850). The calibration result in Figure 2c shows the linear relationship between the differential pressure and the fractional resistance change of the cantilever.…”
Section: Piezoresistive Cantilevermentioning
confidence: 99%
“…The sensor used in this study was a MEMS-based piezoresistive cantilever, similar to the sensors that have been developed in our previous studies to measure forces generated by droplets and cells [23][24][25][26][27][28][29] . The cantilever was fabricated from a silicon-on-insulator wafer, whose device Si, box, and handle Si layers' thicknesses were 300 nm, 400 nm, and 300 μm, respectively.…”
Section: Mems-based Acoustic Sensormentioning
confidence: 99%
“…We used MEMS-based cantilever force sensors to investigate how the beating frequency of hiPSC-CMs changes with temperature. The use of silicon-based force sensors for studying cellular forces has advantages in terms of temporal resolution [ 18 , 19 , 20 , 30 , 31 ]. Silicon-based force sensors have temporal resolutions in the order of GHz, and it has been reported that the force can be measured in units of adhesive spots on cells because of their high measurement speed of 400 kHz [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of silicon-based force sensors for studying cellular forces has advantages in terms of temporal resolution [ 18 , 19 , 20 , 30 , 31 ]. Silicon-based force sensors have temporal resolutions in the order of GHz, and it has been reported that the force can be measured in units of adhesive spots on cells because of their high measurement speed of 400 kHz [ 31 ]. The present study was based on these previous studies, and the kHz-order sampling rate enabled the accurate detection of the timing of the beats.…”
Section: Discussionmentioning
confidence: 99%